European pharmaceutical industry : a micro-econometric analysis of growth dynamics and production location - Zhang, Xiaoheng (Trinity College (Dublin, Ireland). Department of Economics, 2009)
The aim of this thesis is to investigate the industry dynamics of expansion and the location pattern of the European pharmaceutical industry in the Single Market Programme era using micro-econometric approaches.
Keywords: Economics, Ph.D.; Ph.D. Trinity College Dublin.